The obligation of bodies of constitutional justice to appeal to the court - Antsiferov, Nikolay V. (Opción, 2019)
The article analyzes the Constitution of Russia, current legislation, the judiciary practice of the regional constitutional bodies, their postulation history, and the mechanisms for legal obligation’s implementation. The study is based on the application of a general system-structural method. Findings show that the RF Constitutional Court follows the policy of the authorities but simultaneously adheres to centralized constitutionalism. In addition, the objects of normative control were identified and classified.